2013
DOI: 10.1016/j.pscychresns.2013.08.001
|View full text |Cite|
|
Sign up to set email alerts
|

fMRI response to negative words and SSRI treatment outcome in major depressive disorder: A preliminary study

Abstract: Clinically useful predictors of treatment outcome in major depressive disorder (MDD) remain elusive. We examined associations between functional magnetic resonance imaging (fMRI) blood oxygen level dependent (BOLD) signal during active negative word processing and subsequent selective serotonin reuptake inhibitor (SSRI) treatment outcome in MDD. Unmedicated MDD subjects (n=17) performed an emotional word processing fMRI task, and then received eight weeks of standardized antidepressant treatment with escitalop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 55 publications
(94 reference statements)
2
27
0
Order By: Relevance
“…Remitters were found to have higher 5-HT 1A binding in the raphe nuclei compared with non-remitters, although there were no differences in neural areas known to be innervated by serotonin neurones. This finding was interpreted in line with the idea that SSRIs may be most effective in those with increased 5-HT 1A autoreceptor function, who are most likely to experience increased serotonin efflux once these receptors are desensitized as part of repeated SSRI treatment [23]. These effects did not correlate with the DTI findings in the same sample above [8], suggesting they may tap into separate aspects of function.…”
Section: Pretreatment Predictorsmentioning
confidence: 52%
See 1 more Smart Citation
“…Remitters were found to have higher 5-HT 1A binding in the raphe nuclei compared with non-remitters, although there were no differences in neural areas known to be innervated by serotonin neurones. This finding was interpreted in line with the idea that SSRIs may be most effective in those with increased 5-HT 1A autoreceptor function, who are most likely to experience increased serotonin efflux once these receptors are desensitized as part of repeated SSRI treatment [23]. These effects did not correlate with the DTI findings in the same sample above [8], suggesting they may tap into separate aspects of function.…”
Section: Pretreatment Predictorsmentioning
confidence: 52%
“…Another recent study used an emotion-based task as a predictor of treatment response to 8 weeks of escitalopram in 17 patients with depression [23], based on an overlapping patient sample to the DTI study reported above [8]. Lower blood oxygen level-dependent (BOLD) responses to negative stimuli across a large network (including the dorsolateral prefrontal cortex [DLPFC], subgenual ACC, insula, posterior cingulate, caudate, and thalamus) were correlated with improvement following subsequent antidepressant drug treatment.…”
Section: Pretreatment Predictorsmentioning
confidence: 99%
“…Furthermore, one recent study found that patients with higher baseline activity in the ACC while viewing emotional words was associated with poorer response to treatment,72 contradicting findings from previous studies. Although there are some inconsistencies in findings, these are likely a result of confounding factors such as differences in sample characteristics and the type of intervention used.…”
Section: Functional Magnetic Resonance Imagingmentioning
confidence: 68%
“…This has shown some promising recent results, indicating that it may become possible to predict individual trajectories of patients with schizophrenia (Anticevic et al, 2015) or mood disorders (Lythe et al, 2015;Schmaal et al, 2015) from neuroimaging data, or forecast individual treatment responses to psychotherapy (Mansson et al, 2015), antidepressants (DeBattista et al, 2011;McGrath et al, 2013;Miller et al, 2013) and antipsychotics (Hadley et al, 2014;Nejad et al, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%